The effects of probiotics in strengthening immunity against the COVID-19 infection - Yuliana, . (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2022)
A severe form of COVID-19 infection causes increasing in inflammatory cytokines, namely cytokine storm. Therefore, immunity of patients with COVID-19 should be strengthened in order against this infection. This paper aimed to evaluate the possible effects of probiotics in strengthening immunity patients with COVID-19. It is a narrative literature review papers based on PubMed, Science Direct, and Google Scholar databases. The keywords were COVID-19 pandemic, immunity, probiotics. Inclusion criteria were review and research paper. Exclusion criteria were not peer-reviewed journals and unavailable full text. Probiotics are beneficial live microbes, and they are well known for their immune and nutritional properties. The potential roles of probiotics to increase the immune system against the COVID-19 infection need to be studied in further clinical research. Most of the research related to the roles of lactic acid bacteria (LAB) are found in fermented food as probiotics. Many LAB are found in Indonesian fermented foods. Lactic acid bacteria roles are essential in the production of fermented foods. They also give some health benefits such as improving antioxidant activity, increasing antimicrobial agents production, and as probiotics.